Efeito da taxa de aeração, da proporção mássica e da umidade da matriz inicial no processo de biossecagem de lodo anaeróbio - Almeida, Marina da Costa Ribeiro de (Universidade Federal de São Carlos, 2020)
Biodrying is a novel technology that uses dewatered sewage sludge to generate energy. Microbial metabolic heat, which is produced during aerobic degradation of organic matter, and forced aeration turn the sludge into biofuel by removing moisture content. The treatment process is affected by the following characteristics: the number of microorganisms within the matrix, oxygen content, moisture content, and nutrient availability in the substrate, and the performance of the operational procedures. The initial biodrying matrix comprises sewage sludge and bulking agents (sawdust and feed), which operate in structuring, nutrition, and moisture content correction. The goal of this study was to analyze the biodrying treatment processes and operations as well as to evaluate the influence of aeration rate, mass ratio, and moisture content in the initial matrix. Bibliometric analysis and papers study drove the arrangements and analysis processes. Eight biodrying trials were carried out in the laboratory on different durations (16, 20, and 24 days). Trials 1, 2, 7, and 8 contained both sludge and bulking agents, while trials 3, 4, 5, and 6 had only bulking agents. The biodrying matrix was mixed manually in Trials 1 and 2 every four days and in the others trials according to the temperature decrease. Forced aeration was continuous (constant or variable) in all trials. The continuous and constant aeration rate for Trials 1 and 2 was 1 L.min-1.kgTS-1; for Trials 5, 7, and 8 was 2 L.min-1.kgTS-1; and for Trial 6 was 3 L.min-1.kgTS-1. The aeration rate (continuous and variable) for Trials 3 and 4 was 1 and 2 L.min-1.kgTS-1, respectively. Both aeration rates were raised to 3 L.min-1.kgTS-1 on day 20. On day 22, the rates were raised again to 4 L.min-1.kgTS-1. It was found that anaerobic sludge dewatered in a mechanical system has a low Lower Heating Value (LHV) on a wet basis (845 kJ.kg-1), thus requiring treatment processes such as biodrying to enable its energy use. Trials 7 and 8 achieved the most efficient results, reaching the thermophilic phase, reducing the moisture content from 62.33 and 61.48% to 46.73 and 29.36%, and reducing the mass by 48.47 and 60.09%, respectively. Trial 8 achieved the lowest moisture content and the highest LHV on a wet basis (10,083 kJ.kg-1), making it the most feasible condition for energy use. In conclusion, the initial matrix moisture content around 60%, aeration rate greater than or equal to 2.0 L.min-1.kgTS-1, and mass proportion of 6:1:5 (sludge:sawdust:feed) present better results involving temperature range and reduction of mass and moisture content, and therefore sewage sludge energy use.
Effect of aeration rate, mass ratio, and initial matrix moisture content on anaerobic sewage sludge biodrying
Keywords: Biossecagem; Lodo de esgoto; Proporção mássica; Taxa de aeração; Umidade da matriz; Biodrying; Sewage sludge; Matrix ratio; Aeration rate; Moisture content; ENGENHARIAS